Integrated Calculation and Coupled Dynamic Analysis of a Concrete Semi-Submersible Floating Wind Turbine in Offshore Deep Water Area - Jiahao CHEN; Yifan GAO; Ziwei YIN; Can ZHENG; Xiaoqi QU (南方能源建设, 2024)
[Introduction] The research aims to explore the integrated calculation method of a 10 MW semi-submersible floating wind turbine, and analyze its coupled dynamic response characteristics in 40～50 m offshore deep water areas. [Method] A 10 MW concrete semi-submersible floating wind turbine was taken as an example, and then numerical calculation was carried out by the integrated calculation method, and its coupled dynamic response under rated and survival conditions was statistically analyzed. [Result] The horizontal motion of the platform is mainly affected by the wave force, wind loading and mooring stiffness. The maximum value of motion and mooring tension occur in the survival condition, and the heave motion is mainly affected by the wave, but the mean value of the pitch/roll motion is mainly affected by the wind loading, all of which meet the design specification. [Conclusion] The integrated calculation method better considers the coupled dynamic behavior of floating wind turbines. Due to the limitation of water depth, the optimization of horizontal motion and mooring nonlinearity of offshore floating wind turbines is more important in offshore deep water areas, and the extreme response mainly occurs in survival conditions. The above conclusions provide an important reference for the research and design of the floating offshore wind turbines in offshore deep water area.